An interaction of the copper nanoparticles-ceftriaxone conjugate with protein, lipid, and carbohydrate components of bacterial cell envelope - Simonov, P. V.; Kovalyova, D. O.; Busko, Т. О.; Dmytrenko, О. P.; Kulysh, М. P.; Zabolotniy, М. А.; Kuzmenko, М. О.; Chekman, I. S. (Reports of the National Academy of Sciences of Ukraine, 2016)
A possibility of an interaction of the copper nanoparticles-ceftriaxone conjugate with protein, lipid, and hydrocarbon components of a cell envelope of gram-positive and gram-negative bacteria is studi- ed by the means of quantum-chemical calculations and the optical spectroscopy. It is found out that the positions and half-widths of dipole-allowed optical absorption bands in solutions of the copper nanoparticles-ceftriaxone conjugate with the aforementioned substances are changed. It is shown that the ceftriaxone electronic state is changed because of the intensiﬁcation of its interaction with components of a cell envelope due to the presence of metal nanoparticles.